The neuronal identity bias behind neocortical GABAergic plasticity. Issue 9 (September 2015) - Allene, Camille; Lourenço, Joana; Bacci, Alberto
Highlights Cortical circuits result from highly specific connections between inhibitory and excitatory neuron subtypes. Different neocortical principal neuron (PN) subtypes are preferentially targeted by specific basket cell classes. PNs in different cortical layers express either depression or potentiation of perisomatic inhibition. PNs relaying to subcortical areas tend to potentiate their perisomatic inhibition. PNs connecting to other cortical areas tend to depress their perisomatic inhibition.